Analysis of Misconceptions on Hydrocarbons Using Two-Tier Diagnostic Test Instruments at SMA Pertiwi 1 Padang - Liza, Yulia Mona; Alizar, Alizar; Fitriza, Zonalia; Iryani, Iryani (Entalpi Pendidikan Kimia, 2021)
The concept is an understanding of an individual or a group of people who is expressed in the form of a meaning that produces knowledge in the form of theories, principles and laws. Conception is a person's ability to understand concepts, both those obtained through interaction with the environment and concepts obtained from formal education. The conceptions of students that are different from what the experts agree on are called misconceptions or misunderstandings. Misconceptions of students that appear continuously will interfere with the formation of scientific conceptions and result in learning problems that can affect student learning outcomes. Therefore it is necessary to analyze the misconceptions of students. One of the diagnostic tests that can be used to analyze misconceptions is a two-tier multiple choice test or also known as a two-tier multiple choice, where the first level is the question being tested while the second level contains the reasons for the answer to the first level. This study aims to analyze misconceptions and determine the percentage of students' misconceptions on hydrocarbon material using descriptive methods. The subjects in this study were 27 students of class XI IPA 2 in SMA Pertiwi 1 Padang. The research instrument was a Two Tier Multiple Choice diagnostic test by dividing students' conceptual understanding into the categories of conceptual understanding, misconception, and conceptual misunderstanding. The results showed that the percentage of students' conceptual understanding in the concept understanding category was 32%, misconception was 34%, and did not understand the concept by 35% on hydrocarbon material. Students' misconceptions on hydrocarbon material at SMA Pertiwi 1 Padang were categorized as moderate